2010
DOI: 10.1007/s00167-010-1325-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological risk factors for falls in people with knee osteoarthritis before and early after knee replacement surgery

Abstract: People who undergo knee replacement surgery may be at increased risk of falls both prior to and 4 months following their surgery, primarily due to deficits in knee extension strength and lower limb proprioception. Therefore, interventions to reduce the risk of falls should be implemented early after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
8
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 54 publications
10
124
8
11
Order By: Relevance
“…The same resear chers obtained a mean discrepancy of 2.3º among the controls, which is also lower than the one recorded in the present study [27]. Levinger et al assessed joint proprioception before knee arthroplasty and at four months after the surgery, recording a mean score of 1.8º compared to 1.3º in the control group on both occasions [10]. However, it is difficult to determine the measurement angle and the manner of the test performance, since the report does not provide a detailed description of the methods.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…The same resear chers obtained a mean discrepancy of 2.3º among the controls, which is also lower than the one recorded in the present study [27]. Levinger et al assessed joint proprioception before knee arthroplasty and at four months after the surgery, recording a mean score of 1.8º compared to 1.3º in the control group on both occasions [10]. However, it is difficult to determine the measurement angle and the manner of the test performance, since the report does not provide a detailed description of the methods.…”
Section: Discussioncontrasting
confidence: 47%
“…In nym czyn ni kiem są nie wy rów na ne pro ble my zwią za ne z ukła dem krą że -nia, któ re mo gą po wo do wać na głe sko ki ci śnie nia i za wro ty gło wy po cho dze nia krą że nio we go [7]. Opi sa ne me cha ni zmy i czyn ni ki pro wa dzą do po gorsze nia funk cji lo ko mo cji i zwięk sze nia ry zy ka upadków, któ re nio są za so bą po wa żne kon se kwen cje w po sta ci ogra ni cze nia spraw no ści i sa mo dziel no ści czy dłu gie go unie ru cho mie nia, mo gą ce go pro wa dzić do zgo nu [7,9,10].…”
Section: Wstępunclassified
See 2 more Smart Citations
“…Although several observational studies have shown with reasonable consistency that knee extensor strength is an important determinant of physical function (4,9), evidence for the standing balance-physical function association is limited (4,5,7). In the first place, it is not a universal observation that patients with knee OA had greater standing COP displacements than did healthy controls (3,4,10). Furthermore, 3 cross-sectional studies (4,5,7) in patients with knee OA reported no significant association between standing balance and physical function in either bivariate or multivariable analyses.…”
Section: Introductionmentioning
confidence: 99%